Design and Development of Fee Structure and Analysis Tool - Patil, SS; Nikam, RS (International Journal of Computer Sciences and Engineering, 2020)
In 21st century whole world is dependent on Information Technology where accuracy, trustworthiness, speed have huge impact. The fee collection progression in college is very crucial procedure as fee structure for every student is different. The fee structure & analysis tool is designed and developed for fee distribution sheet and total collection sheet preparation with various reports required at university level and college level. In manual procedure has some chances of human error. This is the reason that many educational institute are shifting from manual process to Fee structure and analysis tool. There are many advantages of Fee structure and analysis tool like paperless system, automatic calculation, and safe and secure etc. The aim of research work is to develop a Fee structure and analysis system tool for college to make fees related activity and process easy, efficient and user friendly.